Proyecto asociativo para la producción de helados de leche en el barrio El Taxo de la parroquia de Cotogchoa, cantón Rumiñahui su distribución en diferentes presentaciones en las ciudades de Quito y Sangolquí - Almeida Cuaspud, Luisa Geovanna (2015)
This project seeks to analyze the feasibility of creating a microenterprise under the focus of popular and solidarity economy in the parish of Cotogchoa. In order to generate employment and income in turn improve the quality of life of this community. Microenterprise is geared towards developing a derivative of unconventional milk such as ice cream (generating value added milk extraction). Marketing and distribution will be made in the field of Chillogallo south of Quito and in the field of Sangolquí, aiming market a total of 41652 potential consumers. The project will have an initial investment of $ 60268, 4 that it will recover in the fourth year. The selling price of the product is $1, 00 by popsicle and $ 6, 00 per liter tub of ice cream. These prices is affordable and compete with other competitors in the market. The business of producing and selling ice milk shows interesting for investors, since the results obtained through financial assessment tools are positive; with an NPV of $56.514, 64 and an IRR of 66%.